Performing an artistic image for canonical and contemporary solo piano music - Cartwright, Peter Mark (My University, 2020)
This thesis explores the concept of the artistic image in Western art music for solo piano through the preparation of both canonical and contemporary repertoire for concert performance. The research is located within the field of artistic research and specifically (following Henk Borgdorff) research in the arts, which assumes no separation between the researcher and the practice of art. Drawing on techniques from two traditions of writing on musical performance, namely the pianist-pedagogical and artistic research literature, the thesis presents two major narratives detailing the creation and practical realisation of an artistic image from the first encounter with a score through to the first and subsequent performances. Chapter one describes this process for the preparation of Schubert’s Sonata in C Minor, D. 958, while chapter two does the same for the contemporary South African composer Alexander Johnson’s Three Incantations. Additionally, in chapter two, findings are presented from participants who performed in a concert of South African music for solo piano which I organised as part of this research. The participants were provided with a list of artistic image techniques and practical methods to realise these prior to the concert and were interviewed about their experiences and engagements with these. This research finds that while the combined narrative account is one of the most effective techniques for developing an artistic image and relating this image immediately to its practical realisation, additional practical concerns need to be considered which are discussed in the concluding section
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in the Wits School of Arts, Faculty of Humanities, University of the Witwatersrand, 2020